APPLICATION OF K-RECORDS IN THE INTERVAL ESTIMATION OF THE VALUE AT RISK MEASURE (VAR) - Dudziński, Marcin; Wasilewska, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2018)
Value at Risk, or shorter – VaR, is a major tool used in the processes related to the risk management of banks and other monetary institutions, as well as in the tasks connected with financial supervision and scrutiny. The VaR measure may be interpreted as the minimum amount of equity that the company should own in order to be able to cover its potential losses. Although many methods leading to VaR estimation have been established so far, there is still no universal and faultless approach of VaR calculation. In our work, the method of VaR estimation consisting in determination of confidence intervals for VaR in terms of the so-called k-records has been described and used. The proposed approach is illustrated with use of an example from banking sector, concerning the stock prices of PKO BP Bank in the period between 13.01.2017 and 22.03.2018.